Diagnosis of Superior Vena Caval Obstruction without Syndrome - Kehr, M. D.; Petrovich, Z.; Krishnamurthy, G. T.; Blahd, W. H. (Nuklearmedizin - NuclearMedicine, 1976)
Ten patients with known malignant intra-thoracic tumors and no evidence of superior vena cava syndrome were evaluated by means of scintillation camera superior venacavograms. Four of the ten patients proved to have unsuspected involvement of the superior vena cava or its tributaries. The scintillation camera superior venacavogram provides a quick, safe, and accurate method of evaluating the patency of the SVC and its tributaries. We suggest that it should be routinely performed on all patients prior to beginning radiation therapy for malignant intra-thoracic tumors.